2023
DOI: 10.1021/acsaem.3c00382
|View full text |Cite
|
Sign up to set email alerts
|

Low Cost and Strongly Adsorbed Melamine Formaldehyde Sponge Electrolyte for Nontraditional Quasi-Solid Dye-Sensitized Solar Cells

Abstract: Currently, the high cost and the time-consuming preparation of electrolytes of quasi-solid-state dye-sensitized solar cells (QS-DSSCs) remain the key issue for the large-scale commercial fabrication of DSSCs. In this work, we propose a quasi-solid electrolyte based on a conductive melamine formaldehyde (MF) sponge scaffold for the fabrication of QS-DSSCs, which are MXene-MF, rGO-MF and PEDOT:PSS-MF. The three-dimensional porous structure in MF can quickly adsorb and store electrolytes, which shows high wettabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…On this basis, the development of novel electrolytes deserves further research for further enhancing the photovoltaic performance. 130–133…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, the development of novel electrolytes deserves further research for further enhancing the photovoltaic performance. 130–133…”
Section: Discussionmentioning
confidence: 99%
“…[193] At present, Zhicheng et al reported a high PCE of 26.92 % under indoor light condition (1000 lux) using a melamine formaldehyde sponge electrolyte in ss-DSSC and realized the stability of c.a. 90 % after 1000 h. [194] In this work, the mighty sponge was soaked in three type of various conducting fillers by immersing in electrolyte and prepared the quasi-solid electrolyte such as MXene-MF, rGO-MF, and PEDOT: PSS-MF (shown in Figure 25a). The obtained composite sponge electrolyte layer was employed between the photoanode and the counter electrode to assemble three quasi-solid electrolyte DSSCs.…”
Section: Ss-dspv Under Indoor Light Conditionsmentioning
confidence: 99%
“…The enhancement in J sc and FF under indoor light condition, is possibly due to MF fillers. [194] Copyright (2023), with permission from American Chemical Society.…”
Section: Ss-dspv Under Indoor Light Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These additives can control the potential of the redox couple, the surface state of the TiO 2 semiconductor, the shift in the conduction band edge, and the interfacial charge recombination through being incorporating in small amounts [ 20 ]. Ti 3 C 2 T x MXene was introduced as an additive for electrolytes to improve the photovoltaic performance of quasi-solid-state DSCs [ 21 , 22 ]. Sun et al reported that, via the addition of Ti 3 C 2 T x MXene to a quasi-solid-state electrolyte composed of an I − /I 3 − redox couple and a melamine-formaldehyde (MF) sponge, the average PCE of the DSCs under a room light condition (1000 lux) was improved by 26.92% from that of the reference cell without MXene (23.35%) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%